La gestion par bassin versant : du principe écologique à la contrainte politique – le cas du Mékong - Bastien Affeltranger; Frédéric Lasserre (VertigO)
Basin-wide management for water-related projects and land-use planning is a principle or sustainable development. On the Mekong basin, governments, aid agencies and non-governmental organisations rely on this principle to justify their claims.Yet, most stakeholders see basin-scale institutional development as a constraint, and are not willing to support it. This paper analyses the reasons to this reluctance.